Wild java medaka fish (Oryzias javanicus bleeker) as a tool for toxicological test of heavy metals in estuarine areas in Malaysia - Khodadoust, Daryoush (2012)
Pollution of diverse environments is a result of population increase and industrialization in the Coastal areas and estuaries. Biomonitoring offers an appealing tool for the assessment of metal pollution in the aquatic ecosystem and for this reason there is a need for a suitable tool to assess coastal pollution. The overall hypothesis of this dissertation was to introduce Oryzias javanicus (Java medaka) fish as a new organism for ecotoxicological studies in the coastal and estuary areas. It was discovered that the Java medaka fish is available in all sizes and of all ages in all year around in the wild. Following the main aim of the research, biological and ecological condition and sex ratio of Java medaka were studied over a year in the Linggi estuary on the west coast of Peninsular Malaysia. The results showed that the range of measured physico-chemical conditions for the fish to thrive were: salinity (4.93-19.7 ppt), pH (5.6-8.2), temperature (26.1-30.8 ºC), and conductivity (80.3-220.6 mScm-1), O2 (4.3-8.9 mg/l) while the sex ratio was 1:1.6 (male/female). The second objective of this study was to determine the concentration of heavy metals (Cd, Cu, Zn, Fe, Ni and Pb) in different parts of Java medaka fish collected from four sites along the Linggi estuary. The concentration range of heavy metals in different tissues of Java medaka fish varied from 4.41-17.80 μg/g dry weight for Cu, 43.89-78.79 μg/g dry weight for Zn, 7.09-14.79 μg/g dry weight for Pb, 1.96-2.36 μg/g dry weight for Cd, 9.38-14.57 μg/g dry weight for Ni and 93.62-199.17 μg/g dry weight for Fe. The highest concentrations of Pb,Zn, Fe and Cu were found in the gill and the highest concentrations of Cd and Ni were found in the visceral organs; low concentrations of all metals were found in part of the caudal muscle. Sequential extraction technique (SET) was used to evaluate the four fractions (exchangeable, acid-reducible, oxidisable, and residual) in surface sediment of four sites of the Linggi estuary. Relationship of metals between each fraction of sediment and metal concentrations in different parts of fish (especially in the gills) were found between Cd, Fe, Zn and Pb. Therefore, Oryzias javanicus could be a useful biomonitoring agent for these metals in the environments like the Linggi estuary. Acute toxicity of heavy metals (Cu, Zn and Cd) on Java medaka (Orizyas javanicus) fish, were studied in the next step based on O.E.C.D method, the LC50-96 h for Cu, Zn and Cd were determined 5.43 (5.32-5.54), 9.75 (9.65-9.85) and 6.02 (5.83-6.21) mg/l for juveniles and 8.64 (8.34-8.94), 14.32 (13.94-14.70) and 6.63 (6.31-6.95) for adults respectively. In this study induction of metallothionein (MT) and levels of cadmium and zinc of the Java medaka fish were studied after long time (60 days) exposed of juvenile fishes to different concentrations of cadmium and zinc. Results showed statistically significant differences in Cd and Zn and MT’s content in different organs of fish groups exposed to those two metals were found between control group and other groups with different concentrations of metals (p<0.05). Correlation between Cd content and Mt’s in all body sections of Java medaka fish were statistically significant and the correlation was positive; increasing the Cd content in body sections, the Mt’s levels increased also (p<0.01). For Zn all body parts and Zn content significantly correlated (p<0.01) with r values ranging from 0.7343-0.969 whereas liver-MT and muscle-MT were significantly correlated (p<0.05) with value range 0.663. For metallothionein to be an effective biomarker, metal concentrations must be high enough to induce synthesis of the protein. Results of this study indicate that Java medaka fish is more useful and accurate to monitor particular hazardous chemicals and ecotoxicology studies in the estuary and coastal areas. Mapping the geographic area of Java medaka in Malaysia and Java region, genetic researches and study about forbidden chemicals effects such as TBT, recommended for future studies about this fish